Enhancement of Yield Attributes and Seed Yield in Wheat through Source-Sink Manipulation under Different Moisture Regimes - TN TIWARI; AK SINHA; S RAJENDRA PRASAD; SP JEEVAN KUMAR (Seed Research, 2026)
Field experiments were conducted during rabi season in three consecutive years (2012-13, 2013-14 and 2014-15) with two wheat varieties (HI- 1563 and Raj-3765) to determine the effect of GA3 spraying on source–sink relations in wheat crop under normal and moisture deficit conditions. It was observed that spraying of GA3 at the time of anthesis significantly increased the number of seed/spike, biological yield, 1000 seed weight, grain yield and finally seed yield over control. The influence of GA3 @ 100 ppm was higher compared to GA3 @ 50 ppm and control. Yield attributes viz: seed number, 1000 seed weight, grain yield and finally seed yield and its recovery percentage were higher under normal moisture condition than the water deficit condition. Variety HI 1563 displayedthe higher means values over Raj-3765 for almost all the characters.